Marijuana use and its effects in pregnancy - Chabarria, Kristin C.; Racusin, Diana A.; Antony, Kathleen M.; Kahr, Maike; Suter, Melissa A.; Mastrobattista, Joan M.; Aagaard, Kjersti M. (American journal of obstetrics and gynecology, 2016)
It is generally assumed that marijuana is one of the more widely used controlled substances during pregnancy. However, there remains a general paucity of population-based data regarding its use and subsequent perinatal morbidity. We hypothesized that direct patient query during pregnancy regarding marijuana, tobacco, and nicotine use would provide crucial initial population-based data on perinatal risk. Our study sought to examine maternal and neonatal outcomes in pregnancies with reported marijuana exposure, in isolation or in combination with maternal cigarette smoking. We applied a retrospective cohort study design to subjects (n = 12,069) with available information on marijuana use and pregnancy outcomes. Since 2011, we have routinely and directly questioned all gravidae regarding use of marijuana, tobacco, and nicotine-containing products. We examined perinatal outcomes in marijuana smokers vs nonsmokers, as well as patients reporting both marijuana and cigarette smoking. Multivariate analysis enabled determination of adjusted odds ratios for maternal and fetal outcomes, adjusting for confounders. Significance was determined with Mann-Whitney U, χ2, and Fischer exact tests (as appropriate). In all, 106/12,069 reported marijuana use (0.88%), with 48/12,069 (0.4%; or 48/106, 45%) concurrently using cigarettes and marijuana. After controlling for potential confounding variables, while marijuana use alone was not associated with significant adverse outcomes, use in combination with cigarette smoking was significantly associated with increased risk of multiple adverse perinatal outcomes (increased occurrence of maternal asthma [adjusted odds ratio, 2.4; 95% confidence interval, 1.0–5.9]; preterm birth [adjusted odds ratio, 2.6; 95% confidence interval, 1.3–4.9]; decreased [<25th percentile] head circumference [adjusted odds ratio, 2.8; 95% confidence interval, 1.3–4.3]; and decreased [<25th percentile] birthweight [adjusted odds ratio, 2.8; 95% confidence interval, 1.6–5.0]). Maternal pregnancy-related hypertension was not increased in marijuana smokers (adjusted odds ratio, 1.30; 95% confidence interval, 0.681–2.498), or in cigarette smokers (adjusted odds ratio, 1.4; 95%, confidence interval, 0.9–1.9). However, co-users had elevated rates of preeclampsia compared to nonusers (adjusted odds ratio, 2.5; 95% confidence interval, 1.4–5.0). In our initial cohort analysis, after controlling for potential confounders, while marijuana exposure alone was not associated with significant perinatal adverse outcomes, co-use with cigarette smoking rendered increased risk over either alone. Due to observed prevalence of concurrent cigarette and marijuana use, it is of likely importance to counsel patients regarding use in pregnancy.